2017
DOI: 10.1002/14651858.cd003054.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Diet, physical activity or both for prevention or delay of type 2 diabetes mellitus and its associated complications in people at increased risk of developing type 2 diabetes mellitus

Abstract: Analysis 2.4. Comparison 2 Diet plus physical activity versus comparator, Outcome 4 All-cause mortality: age. . . Analysis 2.5. Comparison 2 Diet plus physical activity versus comparator, Outcome 5 All-cause mortality: sex. . . Analysis 2.6. Comparison 2 Diet plus physical activity versus comparator, Outcome 6 All-cause mortality: ethnicity. . Analysis 2.7. Comparison 2 Diet plus physical activity versus comparator, Outcome 7 All-cause mortality: obesity. . Analysis 2.8. Comparison 2 Diet plus physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
204
1
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(246 citation statements)
references
References 210 publications
7
204
1
21
Order By: Relevance
“…Although our research design could not relate to reasons explaining this finding, it might relate to the higher lean body mass and metabolic rate typical to younger people, which accelerate weight reduction. Contrary to our findings, previous studies found older age as a predictor of successful weight reduction and maintenance, probably due to higher motivation, fewer competing demands and more medical triggers . For example, in the Look AHEAD and in the TONE trial with cohort mean ages of 59 and 66, respectively, weight loss was associated with improved control of obesity co‐morbidities …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although our research design could not relate to reasons explaining this finding, it might relate to the higher lean body mass and metabolic rate typical to younger people, which accelerate weight reduction. Contrary to our findings, previous studies found older age as a predictor of successful weight reduction and maintenance, probably due to higher motivation, fewer competing demands and more medical triggers . For example, in the Look AHEAD and in the TONE trial with cohort mean ages of 59 and 66, respectively, weight loss was associated with improved control of obesity co‐morbidities …”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation is that when subjects lose large amount of fat they experience favourable changes in their body shape and motivation, and are thus more motivated to maintain weight . The literature, however, is inconsistent regarding this issue: similar to our results, many studies reported higher baseline BMI as a significant predictor of success in weight reduction and maintenance during short and long follow up periods . However, it was also reported that at extreme baseline BMI (above 35) the probability of weight loss and maintenance success declines…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Type 2 diabetes risk in the US DPP was found to decrease with moderate weight loss; every 1-kg decrease in weight in the lifestyle arm was associated with a 16% reduction in future Type 2 diabetes incidence [29]. A recent Cochrane systematic review and meta-analysis [30] of 11 RCTs including 4511 participants demonstrated a 43% reduction in risk (95% CI 36-50) over a mean follow-up of 3.8 years.…”
Section: Efficacy Trials Of Lifestyle Interventionsmentioning
confidence: 99%
“…The association between vitamin D deficiency and weight gain with IFG was not affected by supplements in our study, but reduced sun exposure, unhealthy food and sedentary behaviour may affect vitamin D levels and diabetes risks …”
Section: Clinical Characteristics Divided Into Vitamin D Deficiency Amentioning
confidence: 99%